Analisis Manajemen Risiko Sistem Pembelajaran Online Pada Perguruan Tinggi Menghadapi Pandemi Covid-19 - Yusyida Munsa Idah; Ronggo Agatha Prima (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2021)
The application of information technology to support a business process should be consistent with the goal to be achieved, for if it is not appropriate it would be risky especially if it was abused. Risk assessment measures are intended to identify the risk profile of information technology, which is then assessed for risk, and then respond to that risk so that there are no adverse effects that such risks can cause. The purpose of this study is to analyze the risk management of the college's online learning information system when facing the covid-19 pandemic with the title